Pericardial Effusion and Adenosine Deaminase False Positivity Due to Parvovirus B19. Issue 9 (September 2015) - Öner, Taliha; Ocak, Seda; Telhan, Leyla; Hatipoglu, Dilek; Dalgic, Nazan
<x xml:space="preserve">Abstract</x> This case is presented to highlight that one of the causes for massive exudative pericardial effusion in a child may be parvovirus B19, and adenosine deaminase can be falsely positive in such patients.